The Impact of Monetary Policy on Bond Returns : A Segmented Markets Approach - Bruce Mizrach; Filippo Occhino (Rutgers University, Department of Economics, 2004)
This paper assesses the contribution of monetary policy to the dynamics of bond real returns. We assume that the monetary authority controls the short-term nominal interest rate. We then model exogenously the joint dynamics of the aggregate endowment and the monetary policy variable, and determine bond real returns endogenously. Market segmentation is introduced by permanently excluding a fraction of households from financial markets. When markets are segmented, monetary policy has a direct liquidity effect on the participants? consumption and marginal utility, on the stochastic discount factor, and on real returns. With full participation, however, real returns are determined by the aggregate endowment only, so monetary policy can affect them only indirectly. Data on bond returns strongly favor the segmented markets model over the full participation model. For maturities up to 2 years, the segmented markets model is able to replicate the sign and the size of the impulse response of bond returns to monetary policy shocks, it correctly predicts the sign of their autocorrelation, and it closely matches their volatility as a function of maturity.
Keywords: E52; E44; G12; 330; Geldpolitik; Rentenmarkt; Kapitalertrag; Volatilität; Marktsegmentierung; Liquiditätseffekt; Cash-in-Advance-Modell; Theorie